2021
DOI: 10.3390/ijms22147546
|View full text |Cite
|
Sign up to set email alerts
|

Understanding In Vitro Tissue Culture-Induced Variation Phenomenon in Microspore System

Abstract: In vitro tissue culture plant regeneration is a complicated process that requires stressful conditions affecting the cell functioning at multiple levels, including signaling pathways, transcriptome functioning, the interaction between cellular organelles (retro-, anterograde), compounds methylation, biochemical cycles, and DNA mutations. Unfortunately, the network linking all these aspects is not well understood, and the available knowledge is not systemized. Moreover, some aspects of the phenomenon are poorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 232 publications
(266 reference statements)
0
4
0
Order By: Relevance
“…It was also shown that there are differences in sequence and methylation patterns within symmetric and asymmetric contexts, possibly indicating the role of methylation in green plant regeneration efficiency (GPRE) ( Bednarek et al, 2021a ). However, studies of TCIV based on sequence and DNA methylation changes indicated the phenomenon’s complexity but could not explain its nature ( Bednarek and Orłowska, 2020b ; Ghosh et al, 2021 ; Bednarek et al, 2021b ). At least to some degree, such the opportunity may be born using Fourier Transform Infrared (FTIR) spectroscopy, which provides signals of relevant functional groups and thus allows the identification of chemical compounds in a sample.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that there are differences in sequence and methylation patterns within symmetric and asymmetric contexts, possibly indicating the role of methylation in green plant regeneration efficiency (GPRE) ( Bednarek et al, 2021a ). However, studies of TCIV based on sequence and DNA methylation changes indicated the phenomenon’s complexity but could not explain its nature ( Bednarek and Orłowska, 2020b ; Ghosh et al, 2021 ; Bednarek et al, 2021b ). At least to some degree, such the opportunity may be born using Fourier Transform Infrared (FTIR) spectroscopy, which provides signals of relevant functional groups and thus allows the identification of chemical compounds in a sample.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression and phenotypic traits might be affected by chromosome structural variation [ 40 , 41 ]. Microspore culture provides an efficient way to produce homozygosity-stabilized lines with mutation introduction such as DNA degradation and DNA sequence changes [ 42 , 43 ]. 4942C-5 with dwarf and compact plant architecture is a double haploid line obtained from microspore culture.…”
Section: Discussionmentioning
confidence: 99%
“…It was also suggested that methylation may participate in GPRE [ 22 ]. Unfortunately, studies of TCIV failed to explain the nature of the phenomenon (for more information on this, see the reviews [ 23 , 24 ]). Therefore, it was hypothesized that it might have a biochemical background.…”
Section: Introductionmentioning
confidence: 99%